Pemanfaatan Biji Lamtoro untuk Pembuatan Kecap dan Pemberdayaan Kelompok PKK di Desa Kaliploso Cluring, Banyuwangi - Alif Nur Laili Rachmah; Yuni Susanti; Ayu Qurota A’yun; Ansori Ansori; Ratri Sekaringgalih (Universitas Muhammadiyah Surakarta, 2023)
The community service program carried out in Kaliploso Village, Cluring District, Banyuwangi Regency is a sharing of knowledge from chemical engineering lecturers and students to the community. The aim of implementing this program is to increase the creativity of the Kaliploso community by using lamtoro seeds as an alternative to soybeans as the basic ingredient for making soy sauce with the addition of special spices. The program implementation method begins with outreach, training in making soy sauce, fostering independent production, to monitoring, and evaluation. First, socialization to the community regarding the natural potential in Kaliploso village, especially on the nutritional content of lamtoro seeds, secondly, training on making lamtoro soy sauce is explained in detail regarding the composition, tools used, and the stages of the soy sauce making process, thirdly, assistance and encouragement for independent production to participants who have formed 4 groups to make lamtoro soy sauce at home, the last stage is monitoring and evaluation carried out to measure the level of success of the program for utilizing the natural potential and community empowerment through training in making lamtoro soy sauce. The impact of the program that has been carried out can ignite the community to be more productive, create products that can add economic value and promote prosperity in Kaliploso village, and the soy sauce product